Highly selective and water-soluble peptidyl chemosensors for copper(ii) and mercury(ii) ions based on a β-hairpin structure - Lu, Ming-Chou; Chiu, Ling-Ying; Chiu, Li-Yang; Lin, Chih-Ying; Horng, Jia-Cherng (Analytical methods, 2013)
Based on a beta -hairpin structure, two new water-soluble peptidyl chemosensors, HP7-H2H11 and HP7-H1H12, were designed and synthesized. In the peptides we implanted histidine as a metal-binding unit and tryptophan as a reporting unit. These two peptides are sensitive and selective to the detection of Cu super(2+) and Hg super(2+) with a detection limit in the range of 0.6 to 1 mu M. The dissociation constants (K sub(d)) of Cu super(2+) binding are smaller than those of Hg super(2+) binding in HP7-H2H11 and HP7-H1H12, indicating that the peptides have a higher affinity to Cu super(2+) than Hg super(2+). pH-dependent fluorescence measurements could be used to discriminate between Cu super(2+) and Hg super(2+) in solution due to the fact that these two metal ions had significantly different quenching effects on the fluorescence of HP7-H2H11 and HP7-H1H12 under alkaline conditions. Circular dichroism (CD) measurements further showed that Cu super(2+) and Hg super(2+) have distinct effects on the secondary structure of the peptides, providing a complimentary means to differentiate Cu super(2+) from Hg super(2+).